Alternate forms of cytochrome c in the mi-1 (poky) mutant of Neurospora crassa - W. A. Scott; H. K. Mitchell (Fungal Genetics Reports, 1965)
Alternate forms of cytochrome c in the mi-1 (poky) mutant of Neurospora crassa